Localisation of iron and zinc in grain of biofortified wheat - Yongfang Wan; Stewart, Theodora; Amrahli, Maral; Evans, Jessica; Sharp, Paul; Velu, Govindan; Hawkesford, Malcolm John; Shewry, Peter (Elsevier, 2022)
The dietary contributions of iron (Fe) and zinc (Zn) from cereals are determined by concentrations, locations and chemical forms. A genetically biofortified wheat line showed higher concentrations of Zn and Fe than three control lines when grown over two years. The mineral distributions determined using imaging (histochemical staining and LA-ICP-MS), sequential pearling and hand dissection showed no consistent differences between the two lines. Fe was most abundant in the aleurone layer and the scutellum and Zn in the scutellar epithelium, the endosperm transfer cells and embryonic axis. Pearling fractions showed positive correlations between the concentration of P and those of Zn and Fe in all fractions except the outermost layer. This is consistent with Fe and Zn being concentrated in phytates. Developing grains showed decreasing gradients in concentration from the proximal to the distal ends. The concentrations of Fe and Zn were therefore higher in the biofortified line than the control lines but their locations did not differ.